Ability of frozen-thawed ram spermatozoa to bind to vitrified homologous oocytes - Marco-Jimenez, F.; Vicente, J. (Spanish Journal of Agricultural Research, 2004)
This study was designed to evaluate the ability of ram spermatozoa (thawed or thawed swim-up selected) to bind to homologous oocytes subjected to different treatments (in vitro matured or immature, fresh or vitrified). Frozen semen from Guirra breed males was tested on 1,267 oocytes harvested from pre-pubertal ewes at an abattoir. Highest proportions of oocytes with bound spermatozoa were recorded when in vitro matured oocytes, whether fresh or vitrified, were coincubated with thawed spermatozoa separated by swim-up (60.8 and 56.8% for fresh and vitrified matured oocytes, versus 9.4 and 11.1% for fresh and vitrified immature oocytes, respectively, p < 0.05). The number of bound spermatozoa per oocyte was also significantly higher for the swim-up selected spermatozoa than the thawed untreated spermatozoa (3.2 +/- 0.5 vs 1.6 +/- 0.7, p < 0.05, respectively), and higher still when fresh in vitro matured oocytes were used (8.3 +/- 0.5).